Computational power of probabilistic bidirectional sticker system in DNA computing - Selvarajoo, Mathuri; Fong, Wan Heng; Sarmin, Nor Haniza; Turaev, Sherzod (CESER Publications, 2015)
Sticker system has been introduced in 1994 as a model for DNA computing using the re-combination behaviour of DNA molecules. A sticker model is an abstract computational model which uses the Watson-Crick complementarity principle of DNA molecules. Starting from the incomplete double-stranded sequences, and by iterative sticking operations, complete double-stranded sequences are obtained. It is known that sticker systems with finite sets of axioms and sticker rules generate only regular languages. Hence, different types of restrictions have been considered to increase the computational power of sticker systems. In a special type of sticker system known as bidirectional sticker system, the sticking operation occurs at both left and right hand side of the axioms simultaneously. Recently, probabilistic sticker systems have been introduced where the probabilities are initially associated with the axioms or strings, and the probability of the generated string is computed by multiplying the probabilities of all occurrences of the initial strings. In this paper, some properties of probabilistic bidirectional sticker system are investigated. We prove that probabilistic bidirectional sticker system can also increase the computational power of the languages generated.